Digital Image Correlation (DIC) and Finite Element Modelling (FEM) assessment on hybrid composite carbon glass fibre under tensile and flexural loading - Ab Ghani, Ahmad Fuad; Jumaidin, Ridhwan; Hussin, Mohamed Saiful Firdaus; Dhar Malingam, Sivakumar; Abdul Munir, Fudhail; Ranom, Rahifa; Mahmud, Jamaluddin (IJENS Publishers, 2020)
Digital Image Correlation results of in plane strain measurement is discussed and synthesized on deviation obtained from Finite Element Modelling strain contour. In plane deformation measurement technique of Digital Image Correlation (DIC) full field deformation on Hybrid Composite C/GFRP with comparison with Finite Element Modelling (FEM).The deformation displacement, in-plane strain xx, in-plane strain yy and in-plane shear strain xy are extracted from strain gauge and digital image correlation (DIC) technique via high-speed camera that captures during the experiment. Proposing the in plane deformation measurement technique of Digital Image Correlation (DIC) on Hybrid Composite C/GFRP with comparison to Finite Element Modelling (FEM) via Median Value.